The advances of genetics research on Hirschsprung's disease - Juntao Ke; Ying Zhu; Xiaoping Miao (Wiley, 2018)
Abstract Hirschsprung's disease (HSCR) is a rare and complex congenital disorder characterized by the absence of the enteric neurons in lower digestive tract with an incidence of 1/5 000. Affected infant usually suffer from severe constipation with megacolon and distended abdomen, and face long‐term complications even after surgery. In the last 2 decades, great efforts and progresses have been made in understanding the genetics and molecular biological mechanisms that underlie HSCR. However, only a small fraction of the genetic risk can be explained by the identified mutations in the previously established genes. To search novel genetic alterations, new study designs with advanced technologies such as genome/exome‐wide association studies (GWASs/EWASs) and next generation sequencing (NGS) on target genes or whole genome/exome, were applied to HSCR. In this review, we summaries the current development of the genetics researches on HSCR based on GWASs/EWASs and NGS, focusing on the newly discovered variants and genes, and their potential roles in HSCR pathogenesis.